Universal access to essential medicines as part of the right to health: a cross-national comparison of national laws, medicines policies, and health system indicators - Katrina Perehudoff (Taylor & Francis Group, 2020)
Background Access to essential medicines for the world's poor and vulnerable has made little progress since 2000, except for a few specific medicines such as antiretrovirals for HIV/AIDS. Human rights principles written into national law can create a supportive environment for universal access to medicines; however, systematic research and policy guidance on this topic is lacking. Objective To examine how international human rights law and WHO's essential medicines policies are embedded in national law for medicines affordability and financing, and interpreted and implemented in practice to promote universal access to essential medicines. Methods This thesis consists of (1) a cross-national content analysis of 192 national constitutions, 71 national medicines policies, and legislation for universal health coverage (UHC) from 16 mostly low- and middle-income countries; (2) a case study of medicines litigation in Uruguay, and (3) a follow-up report of eight right to health indicators for access to medicines from 195 countries. Results Some, but not all, of the 12 principles from human rights law and WHO's policy are embedded in national UHC law and medicines policies (part 1). Even the most rights-compliant legislation for access to medicines is subject to the unique and inconsistent interpretation of domestic courts, which may be inconsistent with the right to health in international law (part 2). Many national health systems for which data were available still fail to meet the official targets for eight indicators of access to medicines (part 3). Conclusions International human rights law and WHO policy are embedded in national law for essential medicines and practically implemented in national health systems. Law makers can use these findings and the example texts in this thesis as a starting point for writing and monitoring governments' rights-based legal commitments for access to medicines. Future research should study the effect of national law on access to medicines and population health.